Aortic proximalization—Zone 0 versus Zone 2: A concept or true challenge?. Issue 9 (10th June 2021) - Tan, Sven Z. C. P.; Lopuszko, Aleksandra; Munir, Wahaj; Adams, Benjamin; Bashir, Mohamad
Abstract: Background: The use of the Frozen Elephant Trunk (FET) device to manage complex surgical pathologies of the aorta (such as acute type A aortic dissection) has gained popularity since its introduction in the early 2000s. Though the distal anastomosis was traditionally performed at aortic Zone 3 (Z‐3‐FET), preference gradually shifted towards Zone 2 (Z‐2‐FET) in favor of improved surgical access and clinical outcomes. This review seeks to elucidate whether proximalization of arch repair to Zone 0 (Z‐0‐FET) would further improve postoperative outcomes. Methods: We performed a review of available literature to evaluate the comparative efficacies of Z‐2‐FET versus Z‐0‐FET, in terms of surgical technique, clinical outcomes, and incidence of adverse events. Results: Z‐0‐FET seems to be associated with a more accessible surgical approach, and shorter cardiopulmonary bypass, antegrade cerebral perfusion, and cardioplegia durations than Z‐2‐FET. Further, Z‐0‐FET is could potentially be associated with a lower incidence of neurological, renal, and recurrent laryngeal nerve injury, as well as mortality and reintervention rates than Z‐2‐FET. This said, Z‐0‐FET is itself associated with significant challenges, and efficacy in terms of postoperative true lumen integrity and false lumen thrombosis is mixed. Conclusion: Current literature seems to suggest that Z‐0‐FET procedures are more straightforward and associated with lower rates of certain adverse events, however, the majority of data reviewed is retrospective. This review, therefore, recommends prospective research into the comparative strengths and limitations of Z‐0‐FET and Z‐2‐FET to better substantiate whether proximalization of arch repair represents a concept, or a true challenge to advance surgical intervention for arch pathologies.